Ч. 3; Преобразователи электрической энергии силовой электроники - Тимошкин В. В. Вадим Владимирович; Михальченко С. Г. Сергей Геннадьевич; Ляпунов Д. Ю. Данил Юрьевич; Глазырин А. С. Александр Савельевич (2023, 2023)
Заглавие с титульного экрана